2002
DOI: 10.1002/cne.10457
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐stimulated cobalt uptake provides selective visualization of neurons expressing AMPA‐ or kainate‐type glutamate receptors in the retina

Abstract: Fast-acting excitatory neurotransmission in the retina is mediated primarily by glutamate, acting at alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) -selective and kainate-selective receptors. To localize these sites of action, cat retinas were stimulated with either AMPA or kainate and processed for histochemical visualization of cobalt uptake through calcium-permeable channels. Treatment with both agonists resulted in staining of A- and B-type horizontal cells and several types of OFF cone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Finally, the kainate receptor subunit GluR5 is not colocalized with the FMB dendrites or with the GluR1 subunit, indicating that a different bipolar cell type expresses this subunit. This result is consistent with findings in cat and ground squirrel retinas showing that AMPA and kainate receptors are expressed by distinct types of bipolar cells (DeVries, 2000;Pourcho et al, 2002;DeVries et al, 2006). Whether FMB cells also express the AMPA receptor subunits GluR2/3 and GluR4, which have been found at low numbers of flat contacts in cat, rodent, and macaque retinas Pourcho, 1996, 1999b;Morigiwa and Vardi, 1999;Hack et al, 2001;Haverkamp et al, 2001a), remains to be determined.…”
Section: Fmb Cells Express Ampa Receptorssupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, the kainate receptor subunit GluR5 is not colocalized with the FMB dendrites or with the GluR1 subunit, indicating that a different bipolar cell type expresses this subunit. This result is consistent with findings in cat and ground squirrel retinas showing that AMPA and kainate receptors are expressed by distinct types of bipolar cells (DeVries, 2000;Pourcho et al, 2002;DeVries et al, 2006). Whether FMB cells also express the AMPA receptor subunits GluR2/3 and GluR4, which have been found at low numbers of flat contacts in cat, rodent, and macaque retinas Pourcho, 1996, 1999b;Morigiwa and Vardi, 1999;Hack et al, 2001;Haverkamp et al, 2001a), remains to be determined.…”
Section: Fmb Cells Express Ampa Receptorssupporting
confidence: 92%
“…Consistently, Pourcho and coworkers (Qin and Pourcho, 1999a;Pourcho et al, 2002) suggested that, in cat retina, there are two types of OFF cone bipolar cell expressing AMPA receptors. On the other hand, in ground squirrel retina, to date, only one type of AMPA-receptor-expressing bipolar cell, the b2 cell, has been found (DeVries, 2000;DeVries et al, 2006).…”
Section: Which Glutamate Receptors Are Expressed By Diffuse Off Bipolmentioning
confidence: 83%
See 1 more Smart Citation
“…10C). Although the immunocytochemical procedures using DAB as the reaction product does not allow for colocalization with macromolecular markers, it does allow for a permanent reaction product, and hence long-term storage without photobleaching, similar to the cobalt uptake studies by Pourcho et al (2002). Figure 10D-H shows five small panels of individual hyperpolarizing bipolar cells that show KA-evoked AGB entry (panels inside black rectangular box).…”
Section: Visualizing Agb Localization With Long-term Permanencymentioning
confidence: 92%
“…An alternative method to understanding retinal circuitry has been to use the gating of organic or nonorganic cations to identify neurons that possess functional receptor channels (Pruss et al, 1991;Marc, 1999a,b;Michel, 2002, 2003;Marc and Jones, 2002;Pourcho et al, 2002;Marc et al, 2003;Sun et al, 2003). One of these approaches has been to use agmatine (1-amino-4-guanidobutane; AGB), a cationic guanidinium analog that permeates activated ionotropic glutamate receptor channels while not permeating other cation channels such as voltagegated Na ϩ and Ca 2ϩ channels or be taken up by Na ϩ coupled transporters (Marc, 1999a,b;Edwards and Michel, 2002;Sun et al, 2003;Kalloniatis et al, 2004).…”
mentioning
confidence: 99%